C1‐INH concentrate for treatment of acute hereditary angioedema: a pediatric cohort from the I.M.P.A.C.T. studies. Issue 1 (22nd November 2012) - Schneider, Lynda; Hurewitz, David; Wasserman, Richard; Obtulowicz, Krystyna; Machnig, Thomas; Moldovan, Dumitru; Reshef, Avner; Craig, Timothy J.
Abstract Background We analyzed the clinical response of pediatric and adolescent hereditary angioedema (HAE) patients to pdC1‐INH in the International Multicenter Prospective Angioedema C1‐INH Trials (I.M.P.A.C.T.) 1 and 2. Methods Patients included in this post hoc analysis of prospectively collected data were between 10 and 18 yr old with type I or II HAE and a documented history of abdominal or facial attacks. Patients received a single injection of pdC1‐INH concentrate (Berinert®, CSL Behring, Marburg, Germany) 20 U/kg. Efficacy end‐points were time from the administration of study drug to onset of symptom relief and time to complete relief of all symptoms. Results Seven pediatric patients were included in I.M.P.A.C.T.1 with only 1 attack analyzed per patient. Median time to onset of relief was 0.42 h and to complete resolution was 8.08 h. No patient experienced a worsening of symptoms during the 0–4‐h assessment period. Nine patients who experienced a total of 115 attacks were included in the analysis of I.M.P.A.C.T.2. Abdominal attacks were rated as 'severe' more frequently than were other types of attacks. The number of attacks per patient ranged from 2 to 42, and study participation ranged from 1 to 38 months. Median times to onset of symptom relief and to complete symptom resolution were 0.49 h and 14.1 h, respectively. Of 4 treatment‐emergent adverse events in both studies, only 2 were considered related to treatment. Conclusions Study results showed that outcomes with pdC1‐INH treatment of HAE in pediatric patients are comparable with outcomes in adults.